2021
DOI: 10.1155/2021/5591456
|View full text |Cite
|
Sign up to set email alerts
|

Optimum Energy Flow Management of a Grid-Tied Photovoltaic-Wind-Battery System considering Cost, Reliability, and CO2 Emission

Abstract: The main goal of this paper is to explore the performance of a residential grid-tied hybrid (GTH) system which relies on economic and environmental aspects. A photovoltaic- (PV-) wind turbine- (WT-) battery storage system with maximizing self-consumption and time-of-use (ToU) pricing is conducted to examine the system efficiency. In so doing, technical optimization criteria with taking into consideration renewable energy benefits including feed-in-tariff (FIT) and greenhouse gas emission (GHG) reduction are an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 31 publications
0
6
0
Order By: Relevance
“…The results obtained showed that an optimal sharing of power between the main network and the microgrid reduces these costs significantly. An energy management strategy based on a hybrid algorithm has been proposed, in [3], for a grid-integrated residential system to optimize daily operating costs and CO2 emissions. Aghdam et al [13] proposed a procedure for energy management between multi-microgrid systems which takes into consideration the stochastic character of renewable energies and the cost of degradation of batteries.…”
Section: − Literature Reviewmentioning
confidence: 99%
“…The results obtained showed that an optimal sharing of power between the main network and the microgrid reduces these costs significantly. An energy management strategy based on a hybrid algorithm has been proposed, in [3], for a grid-integrated residential system to optimize daily operating costs and CO2 emissions. Aghdam et al [13] proposed a procedure for energy management between multi-microgrid systems which takes into consideration the stochastic character of renewable energies and the cost of degradation of batteries.…”
Section: − Literature Reviewmentioning
confidence: 99%
“…The light power is directly converted into energy by the solar cells. The energy E PV generated by the PV generator is computed as follows 34 :…”
Section: Pv Generatormentioning
confidence: 99%
“…14 The published work on PV-based charging systems covers system design, vehicle-to-grid (V2G) operations, power management, and electricity bill reduction in smart homes. [15][16][17][18][19][20][21] Because all these methods involve a greater standard over a long duration, they cannot tolerate unexpected system perturbations such as rapid irradiance shifts. It has been demonstrated by Thang et al 22 that a sliding-mode control can be used to enhance the robustness of the output voltage of the DC bus to bridge this gap.…”
Section: Introductionmentioning
confidence: 99%
“…The published work on PV‐based charging systems covers system design, vehicle‐to‐grid (V2G) operations, power management, and electricity bill reduction in smart homes 15‐21 . Because all these methods involve a greater standard over a long duration, they cannot tolerate unexpected system perturbations such as rapid irradiance shifts.…”
Section: Introductionmentioning
confidence: 99%